Related Factors to Exclusive Breastfeeding to Postpartum Mothers - Anita Indra Afriyani; Indah Wulaningsih; Novita Sari; Nor Khalimah (Indonesian Journal of Global Health Research, 2022)
One of the indicators in achieving the Sustainable Development Goals (SDGs) until 2030 is maternal and child health. Exclusive breastfeeding is the give of breast milk only without other food and drink to the baby except vitamins, minerals or drugs in the form of drops or syrup, from birth to 6 months of age. 45 post partum mothers do not have good milk production and babies get formula milk. Knowing the factors related to exclusive breastfeeding for postpartum mothers at Public Health Center Kedung I Jepara. Used a quantitative correlational Two Group Pre-Test Post-Tes design with a sample of 36 postpartum mothers who breastfeed their babies. There is a relationship between postpartum mother's knowledge and exclusive breastfeeding (P = 0.018), there is no relationship between postpartum mother's education and exclusive breastfeeding (P = 0.112), there is a relationship between postpartum mother's work and exclusive breastfeeding at Public Health Center Kedung I Jepara (P = 0.02). Comprehensive monitoring is needed from health care workers to ensure postpartum mothers provide exclusive breastfeeding.